Polymer foams as advanced energy absorbing materials for sports applications—A review - Tomin, Márton; Kmetty, Ákos (Journal of applied polymer science, 2022)
The use of polymer foams is becoming increasingly important due to the attainable weight reduction and value‐added properties. The development of foam structures is a popular research area as they have outstanding energy absorbing capability, which is related to the special deformation mechanisms of the cell structure (cell wall buckling and collapse of the cells). This property is exploited by the sports industry, where the main task of such products is to protect the health of the athlete and to ensure safe sports conditions. This review provides a comprehensive presentation of the advanced energy absorbing applications of polymeric foams in sports. The article presents in detail the processing technologies of polymer foams, as well as the sports‐specific regulations which contain the requirements for sports products. The impact damping of polymeric foams is typically determined by falling weight impact tests, which were used in several previous studies. However, it is a great challenge to compare the published results, as the test parameters and the tested materials are different. Currently, an unexplored field of research is the detailed study of multilayer sandwich foam structures. Understanding the effect of layer order on mechanical properties would help researchers achieve a major improvement in this field.